Transfer-Appropriate Processing in the Context of Complex Visual Structures and the Testing Effect - Rice, Melissa A. (Tufts Archival Research Center, 2017)
The present study contributes to existing learning and memory literature by investigating whether the testing effect facilitates the learning of complex visual stimuli and by further examining transfer-appropriate processing in the context of the testing effect.